Functional Cellulose Nanocrystal-Alginate Hydrogel Beads Prepared From Oil Palm Fronds For The Adsorption Of 4-Chlorophenol In Aqueous Solution - Hamidon, Tuan Sherwyn (2023)
The present study aimed to develop efficient cellulose nanocrystal-based hydrogel beads in treating simulated wastewater contaminated with 4-chlorophenol. Initially, cellulose nanocrystals (CNCs) were extracted from oil palm fronds (OPF) employing the sulphuric acid hydrolysis method along with various pretreatments.